'His "old humble Opinion"': John Keats and Bob Harris. (April 2015) - Page, Kenneth
<x content-type="archive" xml:space="preserve">Abstract</x> This essay explores a memoir of Robert Harris, the mysterious 'Bob Harris' mentioned by Keats in two of his letters to his brothers George and Tom.